Vaginal Isosorbide Mononitrate and Misoprostol for Induction of Cervical Ripening Prior to 1st Trimester Surgical Evacuation of Retained Products of Conception - Shafique, Uzma Shafique; Farzana Kazmi, Farzana Kazmi; Farah Rehana, Farah Rehana (Journal of Rawalpindi Medical College, 2010)
Background: To compare the effect of vaginal isosorbide mononitrate with misoprostol for cervical ripening in women with first trimester missed abortion before surgical evacuation of uterus. Methods: In this randomized controlled trial, hundred patients, requiring cervical ripening and surgical evacuation of retained products of conception, were divided into two equal groups. Misoprostol (400 microgram) was placed in posterior vaginal fornix in Group A patients and dose was repeated every three hours upto 4 doses or until reaching cervical ripening. Isosorbide mononitrate (80milligram) was given vaginally in Group B patients and dose was repeated every three hours up to 4 doses or until reaching the cervical ripening. Results: There was no significant difference in side effects between two groups. However Misoprostol was more effective than Isosorbide Mononitrate (IMN) to cause cervical ripening before suction termination of first trimester missed abortion . Conclusion: Nitric oxide donor “Isosorbide mononitrate” is less effective than “Misoprostol” to induce cervical ripening prior to first trimester surgical evacuation of retained products of conception and both drugs are associated with a high frequency of side effects